Delving into female breast cancer: Distinct disease-specific survival outcomes between invasive lobular and ductal carcinomas revealed by propensity score matching. - Wu Zhang; Yuquan Huang; Ye Zhou; Jiaojiao Xue; Shan Gao; Lin Kang; Jian Shi; Tao Zhou; Yalong Duan; Sihan Guo; Qingxia Li (PLoS ONE)
Purpose The difference in prognosis between invasive lobular carcinoma (ILC) and invasive ductal carcinoma (IDC) is still controversial in the academic community. Resolving this controversy can help to more accurately determine patients' prognosis, provide further personalized treatment, alleviate unnecessary psychological burden for some patients, and provide direction for further fundamental research. Patients and methods A retrospective cohort study was conducted using the SEER Research Plus Data 8 Registries, Nov 2021 sub (1978-2019), including female breast cancer patients diagnosed with ILC or IDC between 2010 and 2015. Univariate and multivariate Cox regression analyses were performed, and key covariates affecting prognosis were selected. Propensity score matching (PSM) was employed to match patients, and balance tests were conducted to evaluate covariate distribution. Disease-specific survival (DSS) differences between the matched IDC and ILC groups were compared. Results Following PSM, the covariate differences between the IDC and ILC groups were significantly reduced. The survival analysis revealed a significantly better prognosis for the IDC group than the ILC group (Log-rank test p < 0.001), with a 28.0% increased risk observed in the ILC group. Conclusion This study provides evidence supporting the existence of significant differences in prognosis between IDC and ILC patients after rigorous matching. The IDC group displayed a significantly better prognosis than the ILC group. Notably, these findings have implications for personalized treatment in clinical practice and contribute to the ongoing academic debate on survival differences between IDC and ILC. However, further research is needed to investigate the biological mechanisms, gene expression, and signaling pathway disparities between IDC and ILC, aiming to provide more targeted guidance for clinical decision-making.